Integrating Local Culture into IPS Learning: Development and Validation of a Contextual LKPD for Elementary School - Chumi Zahroul Fitriyah; Dyah Ayu Puspitaningrum; Sita Aprilia Rokhmah (Universitas Pendidikan Ganesha, 2026)
The integration of cultural diversity into learning plays an important role in shaping students' character and cultural awareness from an early age. Through contextual and environmentally relevant learning, students not only understand the material cognitively but also internalize the cultural values that develop in their communities. The learning process that emphasizes local culture also helps students feel closer to the material because it is directly related to their daily experiences. Thus, learning becomes more meaningful and participatory, encouraging active student involvement in the classroom. This study aims to describe the development process and analyze the validity, feasibility, and effectiveness of LKPD based on Jombang local culture in the fourth-grade Social Studies subject with the material of Indonesian cultural richness. The study used the Research and Development method, involving teachers and students as test subjects. It employed data collection methods such as interviews, questionnaires, and learning outcome tests to obtain comprehensive, accurate data. The development stages were carried out systematically, starting with needs analysis, design, and field product trials. The results showed that LKPD was in the very feasible and very practical categories based on expert assessments and user responses, and that it improved student learning outcomes at a moderate level. These findings indicate that LKPD based on Jombang local culture is effective as contextual teaching materials, strengthening understanding of the material and fostering students' cultural identity and character sustainably in elementary schools.